A simple model for studying multilayer adsorption of noninteracting polyatomic species on homogeneous and heterogeneous surfaces - Sanchez Varretti, Fabricio Orlando; García, Guillermo Daniel; Ramirez Pastor, Antonio Jose; Romá, Federico José (American Institute of Physics, 2009)
Fil: Sanchez Varretti, Fabricio Orlando. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Luis. Instituto de Física Aplicada "Dr. Jorge Andrés Zgrablich". Grupo Vinculado Bionanotecnología y Sistemas Complejos | Universidad Nacional de San Luis. Facultad de Ciencias Físico Matemáticas y Naturales. Instituto de Física Aplicada "Dr. Jorge Andrés Zgrablich". Grupo Vinculado Bionanotecnología y Sistemas Complejos. - Universidad Tecnológica Nacional. Facultad Regional San Rafael. Grupo Vinculado Bionanotecnología y Sistemas Complejos; Argentina